Admission Rates Following Day-Case Major Otologic Surgery: A Systematic Review. Issue 9 (October 2021) - Derks, Laura S. M.; Borgstein, Isabelle L. A.; Lammers, Marc J. W.; Kamalski, Digna M. A.; Thomeer, Hans G. X. M.; Grolman, Wilko; Stokroos, Robert J.; Wegner, Inge
Abstract : Objective: To assess whether day-case major otologic ear surgery is a safe and feasible alternative to inpatient surgery, while maintaining equal complication rates, and to identify causes of admission after day-case surgery. Data sources: PubMed, Embase, and Cochrane. Review methods: A systematic search was conducted. Studies reporting original data on the effect of day-case ear surgery on admission rate, patient satisfaction, and/or postoperative complications were included. Risk of bias of the selected articles was assessed using criteria based on the Cochrane Collaboration's tool for assessing risk of bias. Results: A total of 1, 734 unique studies were retrieved of which 35 articles discussing 34 studies were eligible for data extraction. The admission rates ranged from 0% to 88% following day-case endaural surgery, 0% to 13% following day-case stapes surgery, 0% to 82% following day-case mastoid surgery, and 0% to 15% following day-case cochlear implant surgery. Patient and parent satisfaction regarding day-case surgery ranged from 67% to 99%. Five studies comparing day-case and inpatient otologic surgery showed no difference in hearing outcome, postoperative complications, or patient satisfaction. Conclusion: The highest pooled admission rate was seen following day-case mastoid surgery. Studies comparing day-case and inpatient care suggest hearing results and postoperative complication rates in day-case otologic surgery are similar to inpatient otologic surgery in both children and adults. Therefore, day-case major otologic surgery seems to be a safe and feasible alternative to inpatient surgery for both children and adults. Abstract : Supplemental Digital Content is available in the text